'I read comics from a feministic point of view': Conceptualizing the transmedia ethos of the Captain Marvel fan community. (1st September 2017) - Freeman, Matthew; Taylor-Ashfield, Charlotte
The contemporary media industries may be thinking transmedially so to engage their audiences across multiple platforms, but it is not enough to assume that the creation of a coherent brand, narrative or storyworld is enough to explain the specificities and the reasons for why audiences choose (or choose not) to engage in transmedia activities. This article argues for the need to analyse the behaviours and motivations of a media-crossing audience according to a more fluid, ephemeral and value-laden transmedia ethos. Specifically, this article uses Captain Marvel – alongside a wide-scale online survey made up of over 200 of the character's fans – as a case study for examining the politics of transmediality, demonstrating how the migration of the Captain Marvel fan base across multiple platforms and iterations of the character is based not on the lure of interconnected storytelling or world building, but is rather built up of a much more layered transmedia ethos based on feminism, alternativism and a digi-gratis economy.